Specific Features of Giardiasis in Young Children (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Currently, one of the factors determining the health status of the population is socially determined diseases, including parasitic diseases. The prevalence of giardiasis among children of different ages, especially in children's organized groups, is quite high due to the high probability of re-infection with giardia due to closer communication and contact in the group. Giardia affects predominantly the gastrointestinal tract, with damage to the duodenum, biliary system and small intestine being dominant in the clinical picture of the disease. Among children, the incidence of Giardia ranges from 27–70%, with the largest percentage occurring in young children. To accomplish this task, we carried out observation and examination (clinical, laboratory and instrumental) of 65 children aged 2 to 15 years who were treated at the helminthological department of the Bukhara Regional Hospital of Infectious Diseases in 2022. The main clinical symptoms of the disease were abdominal pain, loss of appetite, nausea, irritability and diarrhea. After the use of chemotherapy, all infected patients experienced complete recovery, as evidenced by negative laboratory tests and the absence of clinical symptoms in children.